The Judicial House of Lords 1876-2009 - Blom-Cooper, Louis (OUP OxfordGB, 2009)
Addresses the basic features of the House of Lords as a judicial institution: the origins of its judicial function, its history during the 1870s, it way it has been serviced by officialdom, the relationship between the House and the Court of Appeal , and the very recent process by which the House has been replaced by the Supreme Court. Considers the judges who have served in the House, the role of the Lord Chancellor and the criteria for appointments. Looks at the development of the House between 1876 and 2008. Provides regional and external perspectives on the House. Examines specific areas of the law about which the House has pronounced in the last 133 years.